Baboon syndrome - Nowowiejska, Julia; Baran, Anna; Flisiak, Iwona (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
‘Baboon syndrome’ (BS) is a term primarily used to describe a mercury-induced skin eruption after previous sensitization to this chemical element, which was introduced in 1984 by Andersen et al. [1, 2]. This term is related to the clinical picture of confluent erythematous lesions involving buttocks which resemble red buttocks of baboons [3, 4]. Since then, there have been multiple case reports considering this clinical description but taking into account various pathogenesis: drug-induced and non-drug induced (allergenic and non-allergenic). Therefore, a great confusion regarding this term occurred and some researchers have tried to review this syndrome creating a new classification [2].